Understanding Perceived Parental Rejection in Borderline Personality Disorder: A Qualitative Study - Binte Shahid, Shelina Fatema; Rahman, Muhammad Mahmudur (Journal of Neonatal Surgery, 2025)
Background: Borderline Personality Disorder (BPD) is characterized by emotional instability, impulsivity, and interpersonal relationship issues. Parental rejection has been a significant psychosocial risk factor influencing the development and severity of BPD symptoms. However, there has been minimal research on this issue in the Bangladeshi cultural setting. Objective: The aim of the study was to understand the nature of perceived parental rejection in Bangladeshi patients diagnosed with Borderline Personality Disorder (BPD). Method: A qualitative study was conducted using a grounded theory approach. Semi-structured in-depth interviews were carried out with 22 purposively selected adult participants diagnosed with BPD. Data were analyzed to gain an in-depth understanding of the nature of perceived parental rejection. Results: Data analysis revealed seven categories of perceived parental rejection based on participants’ subjective experiences: authoritarianism, neglect, hostile behavior, lack of acceptance, lack of affection, lack of validation, and lack of protection. These behaviors, though sometimes culturally normalized, were interpreted by participants as emotionally rejecting. Conclusion: The study provides a subtle description of the way individuals with BPD in Bangladesh internalize and assign meaning to parental actions as rejection. The seven categories identified highlight the relational and affective features of rejection as experienced by the participants. They highlight the necessity of cultural sensitivity in clinical assessment and intervention by placing particular emphasis on targeting early relational experiences in BPD treatment..